Marcel Duchamp's Fountain One Hundred Years Later - Kilroy, Robert (Springer International Publishing, 2018)
This book marks the centenary of Marcel Duchamp's Fountain by critically re-examining the established interpretation of the work. It introduces a new methodological approach to art-historical practice rooted in a revised understanding of Lacan, Freud and Slavoj Žižek. In weaving an alternative narrative, Kilroy shows us that not only has Fountain been fundamentally misunderstood but that this very misunderstanding is central to the work's significance. The author brings together Duchamp's own statements to argue Fountain's verdict was strategically stage-managed by the artist in order to expose the underlying logic of its reception, what he terms 'The Creative Act.' This book will be of interest to a broad range of readers, including art historians, psychoanalysts, scholars and art enthusiasts interested in visual culture and ideological critique.